Regulation of biofilm formation in Zymomonas mobilis to enhance stress tolerance by heterologous expression of pfs and luxS - Cao, Lian-Ying; Liu, Chen-Guang; Yang, Shi-Hui; Bai, Feng-Wu (Frontiers in Bioengineering and Biotechnology, 2023)
Zymomonas mobilis is a potential alternative of Saccharomyces cerevisiae to produce cellulosic ethanol with strengths in cofactor balance, but its lower tolerance to inhibitors in the lignocellulosic hydrolysate restricts the application. Although biofilm can improve bacteria stress tolerance, regulating biofilm formation in Z. mobilis is still a challenge. In this work, we constructed a pathway by heterologous expressing pfs and luxS from Escherichia coli in Z. mobilis to produce AI-2 (autoinducer 2), a universal quorum-sensing signal molecule, to control cell morphology for enhancing stress tolerance. Unexpectedly, the results suggested that neither endogenous AI-2 nor exogenous AI-2 promoted biofilm formation, while heterologous expression of pfs can significantly raise biofilm. Therefore, we proposed that the main factor in assisting biofilm formation was the product accumulated due to heterologous expression of pfs, like methylated DNA. Consequently, ZM4::pfs produced more biofilm, which presented an enhanced tolerance to acetic acid. All these findings provide a novel strategy to improve the stress tolerance of Z. mobilis by enhancing biofilm formation for efficient production of lignocellulosic ethanol and other value-added chemical products.